Managing pressure at the free-throw line: Perceptions of elite basketball players - Maher, R.; Marchant, D.; Morris, T.; Fazel, F. (International Journal of Sport and Exercise Psychology, 2020)
Performance pressure is ubiquitous at virtually all levels of competitive sport. In the current study, we drew on the collective experiences of seven elite basketball players, using in-depth semi-structured interviews, to explore how pressure in the free-throw shooting is understood, experienced, and managed from the athletes` perspective. We analysed the data inductively and thematically, with three primary themes identified: (a) influencing variables, (b) mental skills, and (c) management strategies. We discuss the findings, especially in the context of improving performance under pressure and recommend strategies relevant to sport psychologists, basketball coaches and players.